Development of rearing methodology for the invasive Spotted Lanternfly, Lycorma delicatula (Hemiptera: Fulgoridae) - Nixon, Laura J.; Jones, Sharon; Dechaine, Andrew C.; Ludwick, Dalton; Hickin, Mauri; Sullivan, Liam; Elsensohn, Johanna E.; Gould, Juli; Keena, Melody; Kuhar, Thomas; Pfeiffer, Douglas G.; Leskey, Tracy C. (Frontiers in Insect Science, 2022)
Lycorma delicatula, White (Hemiptera: Fulgoridae), spotted lanternfly, is a univoltine, phloem-feeding, polyphagous and invasive insect in the USA. Although a primary host for this species is Ailanthus altissima, tree of heaven, L. delicatula also feeds on a wide range of hosts important to the USA including cultivated grapevines. Due to the need for classical or augmentative biological control programs to reduce impacts of L. delicatula across invaded areas, we developed a laboratory-based rearing protocol for this invasive species. Here, we evaluated the use of A. altissima apical meristems, epicormic shoots, and fresh foliage cut from A. altissima as a food source for rearing newly hatched L. delicatula. On these sources of plant material <20% of L. delicatula developed into adults and no oviposition occurred. However, when young, potted A. altissima trees were used as a food source, >50% of L. delicatula nymphs developed to the adult stage under natural daylengths and temperatures ranging from 20–25°C. The addition of wild grapevine, Vitis riparia, did not increase survivorship or reduce development time. To elicit mating and oviposition, adults were provided with A. altissima logs as an oviposition substrate and maintained under shortened daylengths and reduced nighttime temperatures (12L:12D and 24°C:13°C). This resulted in 2.12 egg masses deposited per female, which was 4× more than when adults were maintained in standard rearing conditions (16L:8D and 25°C). Based on these experiments, we present a protocol for reliably rearing L. delicatula under laboratory and/or greenhouse conditions.